Pengaruh Self Manajement Terhadap Tekanan Darah Ibu Hamil Dengan Hipertensi Di Masa Pandemi Covid 19 Di Wilayah RW 13 Kelurahan Beringin - Heny Prasetyo rini (Jurnal Manajemen Asuhan Keperawatan, 2021)
Hypertension is a condition when the blood pressure is at a value of 130/80 mmHg or more in the measurement for two or more times with an interval of about 6 hours or more. Hypertension is one of the main causes of death for mothers, fetuses and neonates. Hypertension can occur in 10% of all pregnancy cases. During the COVID-19 pandemic, those in the high risk category for Covid 19 are the elderly, pregnant women, babies, children and people who have decreased immune or immune deficiencies. With these criteria, pregnant women are among those who are vulnerable to covid transmission 19. Objective To determine the characteristics of pregnant women including age, parity, family history, multiple pregnancies, pre-existing medical conditions such as DM type 1, obesity, and urinary resistance and to find out the results of blood pressure in pregnant women during the Covid pandemic before and after being given self management. The results of the study, most pregnant women with hypertension during the Covid pandemic had an average age of 20-35 years, multiple parity, no history of multiple pregnancy, no history of DM, hypertension with grade 1 (140-159 mmHg systole and 90-99 mmHg Diastole. And after being given self-management, namely by providing blood pressure monitoring, hypertension control, medication adherence and activity The average respondent had blood pressure with systole 145.18 to 138.22 the difference was 7.04 and blood pressure with diastole 90, 13 becomes 87.15 the difference is 3.02.